NEW HOST RECORDS OF LONCHAEIDAE (DIPTERA) IN BRAZIL AND ASSOCIATED PARASITOID - Marsaro JÃºnior, Alberto Luiz; Strikis, Pedro Carlos; Savaris, Marcoandre; Lampert, Silvana; Adaime, Ricardo (REVISTA DE AGRICULTURA, 2013)
In this paper we report new host records of Neosilba pradoi Strikis & Lerena (3 species), Neosilba certa (Walker) (1 species) and Lonchea sp. (2 species) in Brazil. The parasitoid Pachycrepoideus vindemmiae (Rondani) is associated for the first time in Brazil with a Neosilba species.